Validation of a Simple Bioanalytical Method for the Determination of DRF-6196, a Novel Oxazolidinone, in Mouse Plasma - Dravid, Prajakta V.; Bhamidipati, Ravi Kanth; Mullangi, Ramesh; Srinivas, Nuggehally R. (Arzneimittelforschung, 2005)
An isocratic simple, specific, sensitive and reproducible high performance liquid chromatography (HPLC) method was developed and validated for the estimation of DRF-6196, a novel oxazolidinone in mouse plasma. This method involves a simple liquid/liquid extraction of DRF-6196 and the internal standard (IS; chlorzoxazone, CAS 95-25-0) from plasma into dichloromethane/ethyl acetate mixture that was evaporated under nitrogen. The HPLC analysis was carried out on an Inertsil ODS 2 column using 0.01 mol/L potassium dihydorgen ortho phosphate (pH 3.2) and acetonitrile (65:35, v/v) as mobile phase. The eluate was monitored using an UV detector set at 266 nm. Ratio of peak area of analyte to IS was used for quantification of plasma samples. The retention time of DRF-6196 and IS were 8.2 and 11.1 min, respectively. The assay was linear (r2 > 0.999) in the concentration range 0.1-50 µg/ml. Absolute recovery for analyte and IS was > 94 % from mouse plasma. The lower limit of quantification (LLOQ) of DRF-6196 was 0.1 µg/ml. The inter- and intra-day precision in the measurement of quality control (QC) samples, 0.1, 0.3, 15.0 and 40.0 µg/ml, were in the range 3.64 to 9.51 % relative standard deviation (RSD) and 0.92 to 6.23 % RSD, respectively. Accuracy in the measurement of QC samples was in the range 88.15 to 106.05 % of the nominal values. The analyte and IS were stable in the stability studies viz., benchtop, autosampler and freeze/thaw cycles. The stability of DRF-6196 was established for 1 month at −80 °C. The assay method was successfully applied to a pharmacokinetic study of DRF-6196 in mice.
Keywords: DRF-6196, determination in plasma, method validation, mice, pharmacokinetics; Oxazolidinone derivative